Thioacid Mediated Methods for Peptide Ligation and Cyclisation - Benny, Alby (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
In recent years, peptide-based therapeutics have become the focus of intensive research due to their favourable chemical properties. Consequently, the ability to efficiently synthesise a wide range of structurally diverse peptides in high purity is essential. In particular, the orthogonal reactivity of thioacids compared to the canonical amino acids (AAs) has been previously exploited for peptide chemistry, but their full potential remains underexplored. This thesis details the initial development of novel thioacid-mediated peptide ligation and cyclisation methods to broaden the scope of synthetic peptide chemistry. Chapter 2 outlines efforts to develop a peptide ligation reaction between a C-terminal thioester and an N-terminal thioaspartic acid to form a native amide linkage via a transient thioanhydride intermediate. The thioacid would be reformed post ligation and could serve as a handle for late-stage diversification or could be hydrolysed under mild conditions to the native AA, aspartic acid. The reaction was successfully demonstrated on simple model substrates and attempts to extend the reaction to more complex peptide substrates is outlined. Chapter 3 details the application of the photochemical acyl thiol-ene reaction to cyclise fully unprotected linear peptides containing both an alkene and a thioaspartic acid residue to form macrocyclic peptide thiolactones under both UV and blue LED irradiation. This represents the first reported synthesis of peptide thiolactones under radical-mediated conditions. Chapter 4 details investigation of the dethiocarboxylation of C-terminal thioacid derivatives of AAs under photochemical conditions to yield N-alkylamines. Furthermore, initial scoping studies were conducted to determine whether the C(sp3) radical formed as an intermediate during the dethiocarboxylation reaction could be trapped via an intermolecular addition onto an alkene to form C(sp3) linked cyclic peptides.
APPROVED
Keywords: thioacid; peptide; peptide ligation; peptide macrocyclisation; SPPS; peptide thiolactone; acyl thiol-ene; dethiocarboxylation; thioaspartic acid; aspartic thioacid